Evaluasi Sistem Proteksi Penangkap Petir pada Gedung Rektorat dan Gedung KH AR Fachruddin di Lingkungan Universitas Muhammadiyah Purwokerto - Winarso, Winarso; Ridho, Zyon (Proceedings Series on Physical & Formal Sciences, 2023)
Universitas Muhammadiyah Purwokerto has numerous buildings, including the rectorate and the 55.27-meter-tall K.H. A.R. Fachruddin building, that could be struck by lightning and as a result, it require an efficient lightning arrester system (SPP). This study aims to evaluate the building's lightning safety level in compliance with SNI 03-7015-2004, the General Regulations for Lightning Protection Installation (PUIPP), and the building's lightning arrester system's state. Direct measurements of building structures, lightning arrester system components, lightning arrester conditions, and soil resistance are employed to collect research data using the observational approach. The study calculates the degree of protection in structures in accordance with the General Regulations for Lightning Protection Installation (PUIPP) standards and determines the value of the protection range using SNI 03-7015-2004. Both the KH AR Fachruddin building and the rectorate building have an R index of 14, which means that they both desperately need an efficient lightning arrester. The Rector building's system is only 75% effective, compared to 91% in the KH AR Fachruddin building.